Silencing the Honey Bee (Apis mellifera) Naked Cuticle Gene (nkd) Improves Host Immune Function and Reduces Nosema ceranae Infections - Li, Wenfeng (Appl Environ Microbiol, 2016)
Nosema ceranae is a new and emerging microsporidian parasite of European honey bees, Apis mellifera, that has been implicated in colony losses worldwide. RNA interference (RNAi), a posttranscriptional gene silencing mechanism, has emerged as a potent and specific strategy for controlling infections of parasites and pathogens in honey bees. While previous studies have focused on the silencing of parasite/pathogen virulence factors, we explore here the possibility of silencing a host factor as a mechanism for reducing parasite load. Specifically, we used an RNAi strategy to reduce the expression of a honey bee gene, naked cuticle (nkd), which is a negative regulator of host immune function. Our studies found that nkd mRNA levels in adult bees were upregulated by N. ceranae infection (and thus, the parasite may use this mechanism to suppress host immune function) and that ingestion of double-stranded RNA (dsRNA) specific to nkd efficiently silenced its expression. Furthermore, we found that RNAi-mediated knockdown of nkd transcripts in Nosema-infected bees resulted in upregulation of the expression of several immune genes (Abaecin, Apidaecin, Defensin-1, and PGRP-S2), reduction of Nosema spore loads, and extension of honey bee life span. The results of our studies clearly indicate that silencing the host nkd gene can activate honey bee immune responses, suppress the reproduction of N. ceranae, and improve the overall health of honey bees. This study represents a novel host-derived therapeutic for honey bee disease treatment that merits further exploration. IMPORTANCE Given the critical role of honey bees in the pollination of agricultural crops, it is urgent to develop strategies to prevent the colony decline induced by the infection of parasites/pathogens. Targeting parasites and pathogens directly by RNAi has been proven to be useful for controlling infections in honey bees, but little is known about the disease impacts of RNAi silencing of host factors. Here, we demonstrate that knocking down the honey bee immune repressor-encoding nkd gene can suppress the reproduction of N. ceranae and improve the overall health of honey bees, which highlights the potential role of host-derived and RNAi-based therapeutics in controlling the infections in honey bees. The information obtained from this study will have positive implications for honey bee disease management practices.